2017
DOI: 10.1080/00071668.2017.1379051
|View full text |Cite
|
Sign up to set email alerts
|

Automated early detection of drops in commercial egg production using neural networks

Abstract: ABSTRACT1. The purpose of this work was to support decision-making in poultry farms by performing automatic early detection of anomalies in egg production. 2. Unprocessed data were collected from a commercial egg farm on a daily basis over 7 years. Records from a total of 24 flocks, each with approximately 20 000 laying hens, were studied. 3. Other similar works have required a prior feature extraction by a poultry expert, and this method is dependent on time and expert knowledge. 4. The present approach reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
0
13
0
2
Order By: Relevance
“…Previous studies reported using machine learning models to detect drops in flock-level egg production curves ( Morales et al., 2016 ; Ramírez-Morales et al., 2017 ). Compared with these studies, the current study could identify non-laying birds and facilitate monitoring of health and other issues at an individual bird level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported using machine learning models to detect drops in flock-level egg production curves ( Morales et al., 2016 ; Ramírez-Morales et al., 2017 ). Compared with these studies, the current study could identify non-laying birds and facilitate monitoring of health and other issues at an individual bird level.…”
Section: Resultsmentioning
confidence: 99%
“…It consists of several processing units with characteristics like self-adapting, self-organizing, and real-time learning ( Ding et al., 2013 ). ANN has been widely used in poultry production, including estimation of broiler BW ( Amraei et al., 2017 ), total egg production of quails ( Felipe et al., 2015 ), and detecting drops in egg production of laying hens ( Ramírez-Morales et al., 2017 ). The objective of the current study was to improve the previous approach in 2 aspects: 1) To apply the model on the current day; 2) To output more informative results.…”
Section: Introductionmentioning
confidence: 99%
“…Hypothesis tests should be performed to check the significance of differences between ANN configurations [40]. Table 3 shows that statistically significant differences were observed between different architectures.…”
Section: Resultsmentioning
confidence: 99%
“…Data analysis in poultry systems has mainly been performed using mathematical and statistical methods or visual graph analyses. However, the high complexity of biological analyses leads to the use of newer techniques, which allow for the development of more robust systems against unexpected conditions [15]. In this context, the development of alternative and objective tools for the productive management of farms is essential to guarantee the productivity and health of the flocks.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies cited in the literature performed ANNs as a prediction tool in this area. But, in general, the only parameters estimated were the total egg production or anomalies in egg production, selecting inferior number of parameters as input variables [2,8, 15,22]. Regarding poultry health, ANNs have already been used to predict the antimicrobial resistance of Escherichia coli strains [17], the evaluation of lymphocyte depletion in the Bursa of Fabricius [13] and as an objective criteria for histological diagnosis of lymphocytic losses in the thymus by the use of image analysis [5].…”
Section: Discussionmentioning
confidence: 99%